Update on the clinical development of candidate malaria vaccines. - Ballou, W; Arevalo-Herrera, M; Carucci, D; Richie, T; Corradin, G; Diggs, C; Druilhe, P; Giersing, B; Saul, A; Heppner, D; Kester, K; Lanar, D; et al. (2004)
The recent availability of significantly increased levels of funding for unmet medical needs in the developing world, made available by newly created public-private-partnerships, has proven to be a powerful driver for stimulating clinical development of candidate vaccines for malaria. This new way forward promises to greatly increase the likelihood of bringing a safe and effective vaccine to licensure. The investigators bring together important published and unpublished information that illuminates the status of malaria vaccine development. They focus their comments on those candidate vaccines that are currently in or expected to enter clinical trials in the next 12 months.